Chemical Compounds and Decomposition Process from Four Species Leaf Litter As a Source of Organic Matter Soil in Anggori Education Forest, Manokwari - Aditya Rahmadaniarti; Wolfram Y. Mofu (Journal of Sylva Indonesiana, 2020)
Decomposition is a simple change of physical and chemical processes by soil microorganisms—the rate of decomposition process influenced by climate and litter quality factors. Litter content of chemical compounds is essential to determine the litter's quality so that it can be estimated the decomposition process. Leaves litter of Magnolia tsiampacca, Intsia bijuga, Cinnamomum cullilawan, and Aglaia sp., were collected and analyzed for their chemical compounds. Based on lignin and nitrogen content (L/N) value, Cinnamomum cullilawan have the fastest decomposition process. On the contrary, Intsia bijuga has low litter quality, so that has the slowest decomposition process. However, it has the lowest lignin content and high polyphenol content. Our research found that four observed species were able to be used as sources of soil organic matter, although the litter quality is relatively low.